2008
DOI: 10.1261/rna.1185808
|View full text |Cite
|
Sign up to set email alerts
|

The highest affinity binding site of small protein B on transfer messenger RNA is outside the tRNA domain

Abstract: Eubacterial ribosomes stalled on defective mRNAs are released through a mechanism referred to as trans-translation, depending on the coordinated actions of small protein B (SmpB) and transfer messenger RNA (tmRNA). A series of tmRNA variants with deletions in each structural domain were produced. Their structures were monitored by enzymatic and chemical probes in vitro, in the presence and absence of SmpB. Dissociation constants between these RNAs and SmpB from Aquifex aeolicus were derived by surface plasmon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
1
16
1
Order By: Relevance
“…Interaction of free SmpB with ribosomes is salt sensitive in vivo and therefore could be dependent upon the low stringency conditions used in the purification buffers, while its high binding affinity to tmRNA is unquestionable. 21 To our point of view, because SmpB was found in vivo bound to the ribosome and because the intracellular ionic environment can vary, we cannot rule out that this original route for initiating trans-translation might be used, at least under specific cellular conditions. 18 In any case, SmpB acts as a cellular sentinel onto the stalled ribosomes pinpointing those to be rescued.…”
Section: Smpb As the Handyman Of Tmrna During Trans-translationmentioning
confidence: 98%
See 1 more Smart Citation
“…Interaction of free SmpB with ribosomes is salt sensitive in vivo and therefore could be dependent upon the low stringency conditions used in the purification buffers, while its high binding affinity to tmRNA is unquestionable. 21 To our point of view, because SmpB was found in vivo bound to the ribosome and because the intracellular ionic environment can vary, we cannot rule out that this original route for initiating trans-translation might be used, at least under specific cellular conditions. 18 In any case, SmpB acts as a cellular sentinel onto the stalled ribosomes pinpointing those to be rescued.…”
Section: Smpb As the Handyman Of Tmrna During Trans-translationmentioning
confidence: 98%
“…A wealth of biochemical and genetic data have suggested that interactions between SmpB and key nucleotides lying upstream of the resume codon are instrumental in setting the new frame. 21,[70][71][72][73][74] At this step, the position of SmpB has been mapped by the sites of cleavages induced by hydroxyl radical probing of Fe(II) tethered SmpB mutants. Contrary to the A-site position that protruded into the mRNA path toward the downstream tunnel, they localize almost exclusively around the region of the P-site canonical codon-anticodon interaction.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…A number of genetic and structural studies have suggested that the C-terminal tail of SmpB is necessary for accommodation and transpeptidation and ultimately the establishment and selection of the tmRNA ORF (27,30,31). This task might be accomplished by direct interactions between the C-terminal tail of SmpB and the mRNA-like domain of tmRNA (32)(33)(34). Furthermore, recent structural studies have suggested that SmpB specifically recognizes stalled ribosomes through interactions between its C-terminal tail and the ribosomal mRNA channel (28).…”
mentioning
confidence: 99%
“…The only space where it is possible to place SmpB is the loop formed by a single-stranded RNA region (A79-G87) and pK1; in our model, SmpB interacts with one of these elements (A79-G87). Indeed, recently, an alternative binding site for SmpB on the A79-A86 loop was suggested (32). The protection of some nucleotides in this region has also been seen for the SmpBtmRNA complex in solution (33).…”
Section: Introductionmentioning
confidence: 89%
“…Besides the binding to the tRNA-like domain (TLD) of tmRNA, SmpB can interact with the sequence upstream of the resume codon (32,33).…”
Section: Introductionmentioning
confidence: 99%